Genetic population structure of spiny lobster Palinurus delagoae in the south-western Indian Ocean, and the evolutionary history of Palinurus - Gopal, Keshni (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2007.